Understanding egorrhea from cultural-clinical psychology - Sasaki, Jun; Wada, Kaori; Tanno, Yoshihiko (Frontiers in Psychology, 2013)
Based on his observations in Japanese clinical settings, Fujinawa (1972) conceptualized egorrhea syndrome, which includes symptoms such as erythrophobia, fear of eye-to-eye confrontation, olfactory reference syndrome, delusions of soliloquy, delusions of sleep talking, and thought broadcasting. The key feature of this syndrome is self-leakage, a perceived sense that one's personal internal information, such as feelings and thoughts, are leaking out. To reach a more comprehensive understanding of egorrhea, this paper aims to present general overview and reconsider the phenomenon of self-leakage using cultural-clinical psychology as a framework. First, the symptoms of egorrhea are reviewed in relation to other related psychopathologies such as social anxiety disorder (SAD) and taijin kyofusho (TKS), as well as schizophrenia. Second, a series of empirical studies conducted using Japanese non-clinical samples are summarized. The results of these studies form the basis for subsequent discussions, which incorporates the cultural-clinical psychology perspective proposed by Ryder et al. (2011). This paper ends with a general discussion regarding implications for research and clinical practice.